ALTERNATIVE HERBAL DRUGS USED FOR TREATING HAIR DISEASE - Jain, Pushpendra Kumar; Ak, Singhai; Das, Debajyoti; Jain, Pushpendra Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The main objective of present study is to treat Alopecia. Alopecia areata is an unpredictable hair-loss condition. Alopecia is a dermatological disorder with psychosocial implications on patients with hair loss. Herbal systems of medicine have become increasingly popular in recent years. Medicinal plants have been used for the treatment of hair diseases since antiquity. Herbs such as turmeric, fenugreek, ginger, Cyperus rotundus (Nagarmotha), and holy basil are integral parts of ayurvedic formulations. Cyperus rotundus is a well-known ayurvedic herb with purported claims of hair growth promotion. Methods: Extracts are prepared by separating the soluble matter from vegetable tissues by the application of a suitable solvent such as alcohol, water, or ether. The resultant liquid is concentrated by evaporation to obtain a liquid extract or concentrated almost to dryness to obtain the solid extract and its volatile oil. Hair formulation of Cyperus rotundus belonging to family Cyperaceae in the form of herbal formulation (5% herbal cream and oil) was studied and it showed excellent hair growth activity with standard (2% minoxidil ethanolic solution) in Wister albino rats. Results: Hair growth initiation time was significantly reduced to half on treatment with the oil, as compared to control animals. The hair growth promoting effect was evaluated against the control, standard, and test animals at 0, 10, 15, and 20 days with the formulated hair oil and hair cream prepared from the volatile oil extracted from the Cyperus rotundus and the significant hair growth was observed, and the growth was compared with the standard drug used 2% solution of minoxidil. Conclusion: The results of treatment with oil were better than the positive control minoxidil 2% treatment. It holds the promise of potent herbal alternative for minoxidil. Keywords: Alopecia areata, Cyperus rotundus, Hair growth, Extracts, Herbal creams, Hair oil, Hair formulation, Ayurvedic, Cyperaceae. ORCID iD: - http://orcid.org/0000-0002-0439-6060